Fabrication and characterization of copper doped TiO2 nanotube arrays by in situ electrochemical method as efficient visible-light photocatalyst. Issue 7 (August 2015) - Momeni, Mohamad Mohsen; Ghayeb, Yousef; Ghonchegi, Zohre
Abstract: Highly ordered copper doped TiO2 nanotube arrays (CuTiO2 NTs) thin-film were prepared in an aqueous solution containing NH4 F and different concentrations of copper nitrate via the electrochemical oxidation of titanium substrates. The resulting nanotubes were characterized by FE-SEM, XRD, XPS and EDX. The CuTiO2 NTs showed a tube diameter of 40–90 nm and wall thickness of 20–30 nm. Diffuse reflectance spectra showed a shift toward longer wavelengths relative to pure TiO2 nanotubes (TiO2 NTs). The visible light photo-catalytic activity of the CuTiO2 NTs electrodes was evaluated by the removal of methylene blue (MB) dye and the production of hydrogen. The results showed that CuTiO2 NTs samples exhibited better photo-catalytic activity than the TiO2 NTs. This work demonstrated a feasible and simple anodization method to fabricate an effective, reproducible, and inexpensive visible-light-driven photo-catalyst for hydrogen evolution and environmental applications.